2017
DOI: 10.1002/anie.201703806
|View full text |Cite
|
Sign up to set email alerts
|

Cascades in Compartments: En Route to Machine‐Assisted Biotechnology

Abstract: Biological compartmentalization is a fundamental principle of life that allows cells to metabolize, propagate, or communicate with their environment. Much research is devoted to understanding this basic principle and to harness biomimetic compartments and catalytic cascades as tools for technological processes. This Review summarizes the current state-of-the-art of these developments, with a special emphasis on length scales, mass transport phenomena, and molecular scaffolding approaches, ranging from small cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
184
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 153 publications
(190 citation statements)
references
References 173 publications
(343 reference statements)
2
184
0
3
Order By: Relevance
“…It is evident from natural examples that compartmentalized reaction systems offer advantages when intermediate species are prone to escape into competing reaction channels [3][4][5][6][7][8] . The GDH-ST/SC-LbADH hydrogels can be used to investigate this phenomenon because the NADPH consuming LbADH reduction is spatially and kinetically coupled to the NADPH regeneration by GDH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is evident from natural examples that compartmentalized reaction systems offer advantages when intermediate species are prone to escape into competing reaction channels [3][4][5][6][7][8] . The GDH-ST/SC-LbADH hydrogels can be used to investigate this phenomenon because the NADPH consuming LbADH reduction is spatially and kinetically coupled to the NADPH regeneration by GDH.…”
Section: Resultsmentioning
confidence: 99%
“…Towards the goal of the efficient use of renewable biomass as an alternative to petrochemical synthesis for sustainable production processes and energy supply in the future, multistep enzymatic cascade reactions are currently attracting much attention [3][4][5][6][7][8] . Such cascades are abundant in living systems, for instance, to maintain the regulation of metabolic activity or signal transduction [9][10][11] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Them ethod is very mild because protein hybridization is achieved under physiological conditions that do not harm sensitive tertiary and quaternary structures of even complex proteins.O wing to the high surface-coating density,multiplexing capabilities,and various options to regenerate the underlying DNAsurface by simple denaturation protocols,n umerous research papers have meanwhile demonstrated the utility and scope of the DDI method. [32] Also important is the fact that non-natural DNAanalogues,such as peptide nucleic acids (PNA), can be effectively used for DDI approaches,a s demonstrated in proteomics applications. [30] Conductive silicon substrates have also been used for protein and proteome analyses.…”
Section: Dna Chip-based Protein Analysismentioning
confidence: 99%
“…In the present work, the mimetic biomineralization for preparing artificial bone–mimetic composite was used to assemble the enzymes with calcium phosphate to form the immobilized dual enzymes biocatalyst. Aldehyde‐ketone reductase and alcohol dehydrogenase were co‐crystalized with CaHPO 4 at 4 °C to form dual‐enzyme‐inorganic hybrid nanoflowers, which also takes advantage of CaHPO 4 biocompatibility and substrate channeling effects from the dual‐enzyme catalytic cascade reaction . Subsequently, the resulting assembled hybrid nanoflowers immobilized enzymes were applied in biocatalytic synthesis of the chiral alcohol intermediate of Crizotinib using ketone as substrate.…”
Section: Introductionmentioning
confidence: 99%